The Evolution of Computational Thinking in Junior High School Mathematics Learning: A Study of Research Trends 2019-2024 - Wulan Lailasari, Nenden; Aminah, Neneng; Laelasari, Laelasari; Omar, Romarzila (PT Inovasi Pratama Internasional, 2024)
This study aims to analyze articles that meet the criteria of the study of the litelature study of Computational Thinking research trends in Mathematics learning at the elementary level in 2019-2024, the research method uses PRISMA, all articles have been filtered according to the needs of the research. The results of the study revealed that there were two articles that used CT in high school Mathematics learning. The results of the first article of the study showed that high school students had a positive attitude towards programming and high self-efficacy. Meanwhile, the results of the second article research show that educational games can improve students' academic achievement. In addition, this learning approach provides a fun learning environment. This study is expected to be a reference for future researchers